CURRENT STATUS AND PROBLEMS OF THE CATCH STATISTICS ON ANGUILLID EEL FISHERY IN INDONESIA - Honda, Satoshi; Muthmainnah, Dina; Suryati, Ni Komang; Oktaviani, Dian; Siriraksophon, Somboon; Amornpiyakrit, Taweekiet; Prisantoso, Budi Iskandar (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2016)
To compensate the decline of the populations of temperate anguillid eels, tropical anguillid eels become getting attention of East Asian eel market in recent years. Many eel farms have been established in Java Island to culture tropical anguillid eels intending to export the products to East Asia. Since eel farming is reliant on wild-caught anguillid eels such as glass eels, elvers and yellow eels, these eel seeds have been captured in various places in Indonesia. However, it is still unknown that how much of tropical anguillid eels are caught as seeds for eel farming. This study showed two different patterns of the commodity chains of eel seeds from both Sukabumi Regency and Bengkulu Province to the eel farms in Java Island. Official catch statistics on anguillid eels found in both Sukabumi Regency and Bengkulu Province were also analyzed on their features and problems underlied. Considering the sustainable use of anguillid eel resources and critical stances on exploitation of eel seeds from all over the world, the Indonesian government should take an immediate action for developing the national catch statistics on anguillid eel fishery as soon as possible. Â